Valvular calcium load assessment for predicting postprocedural paravalvular leakage: a comparison between surgical aortic valve replacement versus transcatheter implantation. (25th November 2020) - Pollari, F; Pfeiffer, S; Grossmann, I; Vogt, F; Sirch, J; Schwab, J; Fischlein, T
Abstract: Background: Calcification of native aortic valve is a well known variable causing paravalvular leakage (PVL) following transcatheter aortic valve implantation (TAVI). However, there is currently no evidence to support the fact that patients with high calcium load could be better treated with surgical aortic valve replacement (SAVR). Purpose: To assess the utility of preoperative assessment of valvular calcium load through computed tomography in patients affected by severe aortic valve stenosis undergoing SAVR or TAVI. Methods: Between June 2016 and June 2018, 109 candidates for isolated SAVR through minimal invasive access underwent preoperative contrast enhanced multidetector computed tomography (MDCT) for the assessment of valve and aortic calcifications. Calcium load was quantitatively measured using a dedicated software in three regions on interest (aortic valve [AV], left ventricular outflow tract [LVOT] and device landing zone [DLZ], which is the sum of the earlier 2). Clinical, echocardiographic, and MDCT variables were collected and compared to a sample population of 107 patients that underwent TAVI (87 transfemoral, 20 transapical) for native aortic valve stenosis in the same period of time, in the same institution. A univariate and multivariate logistic regression analysis were performed on the whole study population to assess risk factors for the onset of postoperative PVL (any grade, defined as ≥ mild) at discharge. Results: The two study groups were significantly different in terms of age (71.9±5 in SAVR; 81.5±6 in TAVI), gender (36% female in SAVR vs 51% in TAVI), Euroscore II (1.9%±0.8 in SAVR; 4.8%±2.7 in TAVI), annulus perimeter (79.5mm±8.2 in SAVR; 61.8mm±30.5 in TAVI), baseline ejection fraction (57%±8 in SAVR; 51%±12 in TAVI) and severe pulmonary hypertension (2%±13 in SAVR; 26%±44 in TAVI). Calcium load was not different between groups (DLZ 1066 mm 3 ±716 vs 955mm 3 ±639; total calcium in AV 987 mm 3 ±678 vs 879 mm 3 ±601; total calcium in LVOT 78 mm 3 ±130 vs 77 mm 3 ±100). 30-days-mortality was 1.8% in SAVR and 5.6% in TAVI group (p=0.17). At discharge, incidence of all grades PVL was 5.5% in SAVR (0.9% trace, 3.6% mild, 0.9% moderate) and 41% in TAVI group (12.1% trace, 25.2% mild, 3.7% moderate) (p<0.05). On logistic regression on the whole study population, DLZ calcium (OR 1.1, 95% CI 1–1.2 for 100 mm 3, p=0.003) and the use of TAVI (OR 24, 95% CI 7.7–78, p<0.001) were identified as independently associated with the onset of PVL. Conclusions: Aortic valve calcifications are a risk factor for the onset of PVL for both TAVI and SAVR. Nevertheless, the risk increases considerably with the use of TAVI. A deeper anatomical analysis of preoperative MDCT could improve the treatment selection and the outcome of patients affected by aortic valve stenosis. Funding Acknowledgement: Type of funding source: None